2012
DOI: 10.1016/j.trd.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Traffic noise abatement: How different pavements, vehicle speeds and traffic densities affect annoyance levels

Abstract: a b s t r a c tIn this paper, annoyance ratings from traffic noise recorded on cobblestones, dense asphalt, and open asphalt rubber pavements are assessed with regard to car speeds and traffic densities. It was found that cobblestones pavements are the most annoying; also while open asphalt rubber pavement imposes less annoyance than dense asphalt it is not significantly different. Higher car speeds always lead to greater annoyance, as does higher traffic densities. LAeq and LAmax correlate well with annoyance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 6 publications
2
30
1
1
Order By: Relevance
“…along with a good acoustic performance if properly designed. These consolidated granular materials are also widely used in numerous outdoor noise control applications such as noise barriers (3,4) and in ground surfaces (5)(6)(7)(8)(9). In this context, the need to reduce CO 2 emissions while limiting traffic noise (10,11) has prompted the civil engineering industry to focus efforts on development of new environmentally friendly granular materials while providing similar sound absorbing characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…along with a good acoustic performance if properly designed. These consolidated granular materials are also widely used in numerous outdoor noise control applications such as noise barriers (3,4) and in ground surfaces (5)(6)(7)(8)(9). In this context, the need to reduce CO 2 emissions while limiting traffic noise (10,11) has prompted the civil engineering industry to focus efforts on development of new environmentally friendly granular materials while providing similar sound absorbing characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have demonstrated that pavement type and vehicle noise signiicantly afect the levels of environmental noise and associated subjective annoyance measurement [40] and detection levels [41]. Vehicle type afects both detection levels and annoyance ratings with a positive correlation between sound intensity, detection rates and annoyance.…”
Section: Experimental Methods To Measure Traic Noise Annoyancementioning
confidence: 98%
“…Another study on pavement materials compared the noise generated by vehicles crossing cobblestones, dense graded asphalt, and open asphalt rubber pavements (Freitas et al 2012). Comparing the annoyance level, they clarified that the noise, which has been recorded by tire and cobblestone pavement interaction, is the severest compared to the others.…”
Section: Demonstrated That Stonementioning
confidence: 99%